AirSWOT InSAR Mapping of Surface Water Elevations and Hydraulic Gradients Across the Yukon Flats Basin, Alaska. Issue 2 (5th February 2019) - Pitcher, Lincoln H.; Pavelsky, Tamlin M.; Smith, Laurence C.; Moller, Delwyn K.; Altenau, Elizabeth H.; Allen, George H.; Lion, Christine; Butman, David; Cooley, Sarah W.; Fayne, Jessica V.; Bertram, Mark
Abstract: AirSWOT, an experimental airborne Ka‐band interferometric synthetic aperture radar, was developed for hydrologic research and validation of the forthcoming Surface Water and Ocean Topography (SWOT) satellite mission (to be launched in 2021). AirSWOT and SWOT aim to improve understanding of surface water processes by mapping water surface elevation (WSE) and water surface slope (WSS) in rivers, lakes, and wetlands. However, the utility of AirSWOT for these purposes remains largely unexamined. We present the first investigation of AirSWOT WSE and WSS surveys over complex, low‐relief, wetland‐river hydrologic environments, including (1) a field‐validated assessment of AirSWOT WSE and WSS precisions for lakes and rivers in the Yukon Flats Basin, an Arctic‐Boreal wetland complex in eastern interior Alaska; (2) improved scientific understanding of surface water flow gradients and the influence of subsurface permafrost; and (3) recommendations for improving AirSWOT precisions in future scientific and SWOT validation campaigns. AirSWOT quantifies WSE with an RMSE of 8 and 15 cm in 1 and 0.0625 km 2 river reaches, respectively, and 21 cm in lakes. This indicates good utility for studying hydrologic flux, WSS, geomorphic processes, and coupled surface/subsurface hydrology in permafrost environments. This also suggests that AirSWOT supplies sufficient precision for validating SWOT WSE and WSS over rivers, but not lakes. However, improvements in sensor calibration and flight experiment design may improve precisions in future deployments as may modifications to data processing. We conclude that AirSWOT is a useful tool for bridging the gap between field observations and forthcoming global SWOT satellite products. Key Points: The AirSWOT experimental airborne Ka‐band radar interferometer maps water surface elevations and slope, enabling study of lake, river, and wetland flow gradients AirSWOT is a useful validation instrument for the SWOT satellite mission (launch 2021), especially in rivers AirSWOT hardware remains experimental, but recommended modifications to processing, calibration, and experiment design may improve precisions